Modeling of anisotropic properties of double quantum rings by the terahertz laser field - Baghramyan, Henrikh M.; Barseghyan, Manuk G.; Kirakosyan, Albert A.; Ojeda, Judith H.; Bragard, Jean; Laroze, David (Scientific reports, 2018)
The rendering of different shapes of just a single sample of a concentric double quantum ring is demonstrated realizable with a terahertz laser field, that in turn, allows the manipulation of electronic and optical properties of a sample. It is shown that by changing the intensity or frequency of laser field, one can come to a new set of degenerated levels in double quantum rings and switch the charge distribution between the rings. In addition, depending on the direction of an additional static electric field, the linear and quadratic quantum confined Stark effects are observed. The absorption spectrum shifts and the additive absorption coefficient variations affected by laser and electric fields are discussed. Finally, anisotropic electronic and optical properties of isotropic concentric double quantum rings are modeled with the help of terahertz laser field.